Academic writing : a resource for researchers - Blanpain, Kristin, ....- (Leuven : Acco, 2012)
Academic Writing assists new and established researchers in the process of writing and editing English texts. Its objectives are threefold: - to give GUIDELINES for using academic style and language and for writing specific academic genres, such as abstracts, research proposals and especially research articles; - to provide a wide range of vocabulary and grammar RESOURCES for practice and consultation; - to teach learners STRATEGIES for improving and editing their own writing. The book can be used for self-study as well as in the context of an academic writing course. It can also serve as a reference work to be consulted when writing and editing texts.
With index and key
Keywords: Schrijfvaardigheid